2015
DOI: 10.4103/2230-8210.167553
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus in elderly

Abstract: Diabetes mellitus (DM) frequency is a growing problem worldwide, because of long life expectancy and life style modifications. In old age (≥60–65 years old), DM is becoming an alarming public health problem in developed and even in developing countries as for some authors one from two old persons are diabetic or prediabetic and for others 8 from 10 old persons have some dysglycemia. DM complications and co-morbidities are more frequent in old diabetics compared to their young counterparts. The most frequent ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 59 publications
(66 reference statements)
12
95
0
10
Order By: Relevance
“…Socio-demographic variables (e.g. age, gender, marital status, educational level, job, family monthly income) were assessed based on the participants’ self-report (26), information regarding health conditions [history of heart disease, blood pressure (systolic/diastolic blood pressure ≥ 140/90 mmHg) (27), diabetes (fasting glycaemia≥ 1.26 g/l (7.0 mmol/l) (28), hyperlipidemia (self-report of physician diagnosis), obesity (Body Mass Index≥ 30) obtained through the existing medical records (29) and self-perceived health (30) evaluated by a three state single question], lifestyle habits including smoking, physical activity (Several times a week = high, Once a week = medium, Once a month or Less often = low) (31), quality of sleep (evaluated by a three state single question) (13), and finally, to gather data on depression and self-efficacy, we used a Geriatric Depression Scale (GDS≤ 8), and a General Self-Efficacy Beliefs Scale (GSE-10), respectively. The validation of the Iranian version of GDS revealed its good reliability with Cronbach’s coefficients reaching to 92%, also, the ROC analysis showed that cut-off point of 8 with sensitivity of 0.9 and specificity of 0.83 was the most desirable cut point for the Iranian version of GDS (32).…”
Section: Methodsmentioning
confidence: 99%
“…Socio-demographic variables (e.g. age, gender, marital status, educational level, job, family monthly income) were assessed based on the participants’ self-report (26), information regarding health conditions [history of heart disease, blood pressure (systolic/diastolic blood pressure ≥ 140/90 mmHg) (27), diabetes (fasting glycaemia≥ 1.26 g/l (7.0 mmol/l) (28), hyperlipidemia (self-report of physician diagnosis), obesity (Body Mass Index≥ 30) obtained through the existing medical records (29) and self-perceived health (30) evaluated by a three state single question], lifestyle habits including smoking, physical activity (Several times a week = high, Once a week = medium, Once a month or Less often = low) (31), quality of sleep (evaluated by a three state single question) (13), and finally, to gather data on depression and self-efficacy, we used a Geriatric Depression Scale (GDS≤ 8), and a General Self-Efficacy Beliefs Scale (GSE-10), respectively. The validation of the Iranian version of GDS revealed its good reliability with Cronbach’s coefficients reaching to 92%, also, the ROC analysis showed that cut-off point of 8 with sensitivity of 0.9 and specificity of 0.83 was the most desirable cut point for the Iranian version of GDS (32).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in New Zealand, the prevalence of DM has been steadily growing over the last 30 years [3,4] with Māori and Pacific populaitions both disproportionally affected [5] and experaince higher diabetesrelated mortality in later life [4]. Indeed, Type 2 diabetes is an important consideration for older adults, who are at increased risk in terms of onset and disease management due to age-related changes in metabolism and who represent a considerable number of patients [6]. Indeed, disease-related complications, poorly controlled cardiovascular risk, impaired cognitive function, loss of mobility, increased dependency and service use are more common in older adults with diabetes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus was the third most prevalent disease in the study sample. Chentli et al state that, on average, 20% of elderly people suff er from diabetes mellitus, and that another 20% suff er from the disease but have not been diagnosed 13 . Data on this elderly population show that 50% of all bone fractures are femoral fractures.…”
Section: Discussionmentioning
confidence: 99%